Implementation of Restorative Justice in the Handling and Settlement of Narcotic Criminal Actions Permitted by Children - St. Fatima; Nurini Aprilianda; Faizin Sulistio (International Journal of Science and Society, 2022)
Law Number 11 of 2012 concerning the Juvenile Criminal Justice System states that children are a mandate and gift from God Almighty. This research then aims to see how restorative justice is applied in handling and resolving narcotics crimes by children. This research will be carried out using a descriptive qualitative approach. The data used in this research comes from the results of previous research or studies that still have relevance to this research. The results of this study found that, in general, the restorative justice approach used to handle and resolve narcotics crimes by children is still not in accordance and optimal with the provisions in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System